Mechanism and Kinetics of Lipid Bilayer Formation in Solid-State Nanopores - Zeng, Shuangshuang (Langmuir : the ACS journal of surfaces and colloids, 2020)
Solid-state nanopores provide a highly versatile platform for rapid electrical detection and analysis of single molecules. Lipid bilayer coating of the nanopores can reduce nonspecific analyte adsorption to the nanopore sidewalls and increase the sensing selectivity by providing possibilities for tethering specific ligands in a cell-membrane mimicking environment. However, the mechanism and kinetics of lipid bilayer formation from vesicles remain unclear in the presence of nanopores. In this work, we used a silicon-based, truncated pyramidal nanopore array as the support for lipid bilayer formation. Lipid bilayer formation in the nanopores was monitored in real time by the change in ionic current through the nanopores. Statistical analysis revealed that a lipid bilayer is formed from the instantaneous rupture of individual vesicle upon adsorption in the nanopores, differing from the generally agreed mechanism that lipid bilayer forms at a high vesicle surface coverage on a planar support. The dependence of the lipid bilayer formation process on the applied bias, vesicle size, and concentration was systematically studied. In addition, the nonfouling properties of the lipid bilayer coated nanopores were demonstrated during long single-stranded DNA translocation through the nanopore array. The findings indicate that the lipid bilayer formation process can be modulated by introducing nanocavities intentionally on the planar surface to create active sites or changing the vesicle size and concentration